2022
DOI: 10.3390/jintelligence10030050
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Early Word Reading, Phonological Awareness, Early Music Reading and Musical Aptitude

Abstract: A wide range of evidence has demonstrated the impact of music learning on phonological awareness and the development of reading. Music reading, its relationship with linguistic abilities and reading skills are all highly researched areas. However, limited information is available regarding the relationship between early text reading and early music reading. This study examined the relationship between word reading and music reading, musical aptitude and phonological awareness. The sample consisted of 119 Hunga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Reading tests showed to be highly correlating among each other and with response times to target words recorded in the experimental session, which supports their reliability, and that of experimental paradigm in assessing reading proficiency. The higher reading proficiency of musicians, expected on the basis of previous literature (e.g., 24 31 , 34 ), was somewhat surprising given the self-reported reading habits, according to which musicians were used to read less than half as many books per year as non-music students. However, these estimates did not take into account the large number of musical scores that professional musicians read over the course of a year, which, if not full of words, are rich in symbols and equally stimulate reading, attention and ocular mechanisms 44 , 66 .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Reading tests showed to be highly correlating among each other and with response times to target words recorded in the experimental session, which supports their reliability, and that of experimental paradigm in assessing reading proficiency. The higher reading proficiency of musicians, expected on the basis of previous literature (e.g., 24 31 , 34 ), was somewhat surprising given the self-reported reading habits, according to which musicians were used to read less than half as many books per year as non-music students. However, these estimates did not take into account the large number of musical scores that professional musicians read over the course of a year, which, if not full of words, are rich in symbols and equally stimulate reading, attention and ocular mechanisms 44 , 66 .…”
Section: Discussionmentioning
confidence: 77%
“…Specifically for reading, the benefit would come from refined auditory processing and increased phoneme processing, rhythm and phonological awareness skills (e.g., 22 , 23 ) on the one hand, and improved ability to visually decode symbols and quickly translate them into meanings and gestures on the other. Several studies have shown how musical perceptual skills correlate with phonological awareness 24 and reading skills, and may also be predictive of children's reading developmental trajectories 25 28 . For example, an interesting meta-analysis 29 showed that students who received music education scored significantly higher on reading tests than control students.…”
Section: Introductionmentioning
confidence: 99%
“…Reading test showed to be highly correlating among each other and with response times to target words recorded in the experimental session, which supports their reliability, and that of experimental paradigm in assessing reading pro ciency. The higher reading pro ciency of musicians, expected on the basis of previous literature [e.g., [24][25][26][27][28][29][30][31]34], was somewhat surprising given the selfreported reading habits, according to which musicians were used to read less than half as many books per year as non-music students. However, these estimates did not take into account the large number of musical scores that professional musicians read over the course of a year, which, if not full of words, are rich in symbols and equally stimulate reading, attention and ocular mechanisms [66,44].…”
Section: Discussionmentioning
confidence: 96%
“…Speci cally for reading, the bene t would come from re ned auditory processing and increased phoneme processing, rhythm and phonological awareness skills [e.g., [22][23] on the one hand, and improved ability to visually decode symbols and quickly translate them into meanings and gestures on the other. Several studies have shown how musical perceptual skills correlate with phonological awareness [24] and reading skills, and may also be predictive of children's reading developmental trajectories [25][26][27][28]. For example, an interesting meta-analysis [29] showed that students who received music education scored signi cantly higher on reading tests than control students.…”
Section: Introductionmentioning
confidence: 99%
“…Por lo antes expuesto, es fundamental consolidar en los niños en edad preescolar el desarrollo de la conciencia fonológica, en todas sus dimensiones (silábica, fonética e intrasilábica); dado que se define como la capacidad de discriminar e identificar las unidades del lenguaje oral en función de construir fonemas, sílabas o palabras (Meira et al, 2023). En este mismo orden de ideas, Janurik et al (2022) aseguran que dicha habilidad se relaciona con otros procesos de ganancia de saberes indirectos, tales como el aprendizaje musical y las artes en general. Por su parte, la European Commission considera de vital importancia la atención a la primera infancia, ya que, es el primer peldaño de la escalera del aprendizaje permanente; así pues, provee a los niños apoyo profesional para crecer, aprender y prosperar; en ese sentido, ha venido adecuando sus políticas de acuerdo a los nuevos escenarios a partir de un marco de trabajo que permita articular soluciones que conlleven a superar los desafíos que ha dejado la pandemia de Covid-19, lo cual, afectó especialmente el aspecto metafonológico, el cual, es esencial en la adquisición de aprendizajes como la lectura y escritura, entre otros (EC, 2022).…”
Section: Introductionunclassified